2000
DOI: 10.1086/315395
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 as a Cause of Genital Herpes: Impact on Surveillance and Prevention

Abstract: This study compared characteristics of patients who had herpes simplex virus (HSV) type 1 with characteristics of patients who had HSV-2, by use of data from a cross-sectional analysis. Data were collected in an urban sexually transmitted diseases clinic from patients who had positive genital HSV cultures. Overall, 17.1% (95% confidence interval [CI], 14.9%-19.3%) of 1145 genital HSV isolates obtained during 1993-1997 were HSV-1. The proportion of HSV-1 among initial genital herpes infections was higher among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(123 citation statements)
references
References 12 publications
5
113
2
3
Order By: Relevance
“…[14][15][16] Epidemiological studies suggest that oral genital contact is the major risk factor for the acquisition of genital HSV-1. 17 Similar findings have been reported worldwide. In Scandinavia, the seroprevalance of HSV-2 among pregnant women was 33%, 18 and in Canada this rate was 17%.…”
Section: Epidemiology Of Genital Herpessupporting
confidence: 79%
“…[14][15][16] Epidemiological studies suggest that oral genital contact is the major risk factor for the acquisition of genital HSV-1. 17 Similar findings have been reported worldwide. In Scandinavia, the seroprevalance of HSV-2 among pregnant women was 33%, 18 and in Canada this rate was 17%.…”
Section: Epidemiology Of Genital Herpessupporting
confidence: 79%
“…18 Receptive oral sex within the previous 2 months has been associated with an increased likelihood that the initial infection was HSV-1. 19 Despite the apparent increase in orogenital sex seen in many communities, an increased proportion of HSV-2 in orolabial lesions has not been detected in our study (results not shown) or studies undertaken by others. 20 At this time in Melbourne, HSV-1 is more common than HSV-2 in patients under 20 years of age and the likelihood that females will have an HSV-1 genital infection is now similar to that for HSV-2.…”
Section: Discussioncontrasting
confidence: 81%
“…1,2 In addition, HSV type 1 (HSV-1) now accounts for at least 20% and, in some locales, more than 50% of cases of genital herpes in the United States. 3,4 Therefore, managing infants potentially exposed to HSV at the time of delivery is not uncommon, and prevention of the devastating outcomes of neonatal HSV disease is paramount.…”
Section: Introductionmentioning
confidence: 99%